Perkembangan Teknologi Informasi di Indonesia: Tantangan dan Peluang - Khoirunnisya Gita Segara; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
Technology is one of the most significant advances in human civilization, and its impact is still being felt today. Information technology development has been a primary driver of societal transformation in the modern era. This article examines the evolution of information technology within the Indonesian community. The methodology employed in the preparation of this article entails the collation of references to materials from nationally recognised and accredited publications, complemented by a qualitative research approach. The impact of technological advancement in Indonesia is highly significant in terms of influencing interaction patterns and the needs of the Indonesian population. The impact of technological advancement is multifaceted, affecting various aspects of culture, including streaming platforms and virtual reality, which enrich consumption and entertainment experiences. While new opportunities are created for the public, there are also challenges related to information security and privacy that must be addressed. It is of the utmost importance for society as a whole to adapt and manage the positive and negative impacts of technological advancement in order to foster connected and sustainable communities in the digital age.